Examining the relationships between family belonging, interpersonal problem solving and cognitive emotion regulation in individuals with alcohol/substance use disorder - Kalender, Bilal; Bahadır, Erdi (Journal of Dependence, 2025)
Objective: This study aims to examine the relationships between family belonging, interpersonal problem solving and cognitive emotion regulation in alcohol/substance addicted individuals who applied to Istanbul Metropolitan Municipality SUDEM.Method: In the study conducted for this purpose, a questionnaire including demographic information form, Family Belonging Scale, Interpersonal Problem Solving Inventory and Cognitive Emotion Regulation Scale was applied to the participants. A total of 88 people, 28 women and 60 men, participated in the study. As a result of the correlation analysis, significant relationships were found between the concepts.Results: Multiple linear regression analyses were used to examine the dynamic aspects of the relationships. As a result of the regression analyses, it was seen that the partial mediating role of cognitive emotion regulation was significant in the relationship between family belonging and positive problem solving. In addition, it was seen that the partial mediating role of cognitive emotion regulation was significant in the relationship between family belonging and negative problem solving.Conclusion: Deficiencies in individuals' problem solving skills and emotion regulation skills may have negative effects on family belonging.
Keywords: Addiction; family belonging; interpersonal problems; emotion regulation